Effect of Chromium Propionate Level and Feeding Regimen on Finishing Pig Growth Performance and Carcass Characteristics - J. T. Gebhardt; J. C. Woodworth; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; H. S. Cemin; J. A. Loughmiller; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,206 pigs (PIC 359 × 1050; initial BW = 107.9 lb) were used in an 84-d study to evaluate the effects of added dietary chromium (Cr; KemTRACE chromium propionate, Kemin Industries Inc., Des Moines, IA) and feeding regimen on growth performance of finishing pigs housed under commercial conditions. Pigs were placed in mixed-gender pens (27 pigs per pen), blocked by BW, and randomly assigned to 1 of 3 dietary treatments (15 pens per treatment). Diets were corn-soybean meal-based with added dried distillers gains with solubles, and were fed in 4 phases. Treatments were: 1) control, no Cr in grower or finisher formulas; 2) 200 ppb of Cr fed in both grower and finisher; and 3) 200 ppb of Cr fed in grower and 100 ppb fed in finisher. The grower phase was from 108 to 202 lb and the finisher phase was 202 to 273 lb. There was no evidence (P ≥ 0.197) of treatment differences in the grower period. In the finishing period, added Cr resulted in a marginally significant increase (linear; P = 0.061) in ADG (2.03, 2.02, 2.08 ± 0.022 lb/d; 0, 100, 200 ppb added Cr, respectively) with no evidence of an effect (P ≥ 0.148) on ADFI and F/G. For the overall period, there was marginal significance that at least one treatment differed from another (P = 0.086) for ADG. When compared directly, addition of 200 ppb Cr in both grower and finisher increased (P = 0.037) ADG, compared to control with pigs fed 200 ppb added Cr fed in grower, followed by 100 ppb fed in finisher intermediate (1.97, 1.98, and 2.01 ± 0.013 lb/d; 0, 200/100, and 200/200 ppb added Cr, respectively). There was no evidence (P ≥ 0.526) of differences in overall ADFI and F/G. Percentage carcass yield was reduced (P = 0.018) in pigs fed 200 ppb added Cr for both the grower and finishing periods compared to other treatments. There was no evidence of differences (P ≥ 0.206) in HCW, loin depth, backfat, or percentage lean between treatments. In summary, adding 200 ppb of Cr in both grower and finisher formulas increased finishing ADG, led to a marginally significant improvement in overall ADG, but reduced carcass yield.
Keywords: chromium propionate; finishing pigs; duration